2008
DOI: 10.1111/j.1365-2702.2008.02278.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain management – the influence of surgical ward nurses

Abstract: The study shows a need for more accurate pain assessment, since the patient experiences and suffers pain and the nurse determines upon treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 47 publications
3
35
1
5
Order By: Relevance
“…Some studies have revealed that nurses and doctors underestimate patients' pain or desire for analgesia and pain monitoring programmes, consisting of staff education and pain documentation with numeric pain scales, have been shown to improve the compliance with administration of analgesia. 6,11,15,[17][18][19][20] In Europe it is now becoming common practice to document pain scores as part of the routine postoperative observations. This could provide a way to make nursing staff more aware of the problem as patients tend to underreport their pain until it becomes unbearable.…”
Section: Morphine Administrationmentioning
confidence: 99%
“…Some studies have revealed that nurses and doctors underestimate patients' pain or desire for analgesia and pain monitoring programmes, consisting of staff education and pain documentation with numeric pain scales, have been shown to improve the compliance with administration of analgesia. 6,11,15,[17][18][19][20] In Europe it is now becoming common practice to document pain scores as part of the routine postoperative observations. This could provide a way to make nursing staff more aware of the problem as patients tend to underreport their pain until it becomes unbearable.…”
Section: Morphine Administrationmentioning
confidence: 99%
“…der fant man at et knapt flertall av nyopererte ikke opioidavhengige pasienter var blitt spurt om å angi sin smerteintensitet på en smerteskala. sjelden bruk av kartleggingsverktøy kan henge sammen med manglende rutiner, men det kan også knyttes til stigmatiserende, moralistiske og negative holdninger som helsepersonell kan ha til opioidavhengige (8,12,42).…”
Section: Introduksjonunclassified
“…[4][5][6] Therefore, the patient's verbal report of pain is essential and should be accepted as the single most reliable indicator of pain. [4,[7][8][9] Nurses are the health care professionals who spent most of time with the patients [10][11][12] and their role in pain management is essential. In addition; to ensure an effective pain management, there should be an effective pain assessment.…”
Section: ıNtroductionmentioning
confidence: 99%
“…[14] Except these factors; there is another important factor in postoperative pain management which is patients' and also nurses' acceptance of postoperative pain as a normal result of surgery. [11] On the other hand, the pain rating scale used takes an important role on underestimation of pain. Usage of Verbal Rating Scales which the patient verbally describes the level of his pain is not sensitive enough to expose the change in pain level.…”
Section: ıNtroductionmentioning
confidence: 99%
See 1 more Smart Citation